COMBINED NEMATOCIDAL EFFECT OF NONACOSAN-10-OL AND 23A-HOMOSTIGMAST-5-EN-3Β-OL ON MELOIDOGYNE INCOGNITA (KOFOID AND WHITE) CHITWOOD - I. Naz; Saifullah; S. Hussain; J. E. Palomares-Rius; M. Ahmad; A. Ali; M. U. Rashid; F. Bibi (Journal of Animal and Plant Sciences, 2016)
The synergistic effect of three phytochemicals, nonacosan-10-ol, 23a-homostigmast-5-en-3β-ol and cis- and trans-protopinium were assessed in four combinations and three concentrations (5, 50 and 100 µg ml-1) against Meloidogyne incognita, in vitro and in planta on the tomato cultivar Riogrande. Additionally, an in vitro phytotoxicity test on tomato seedlings was performed with the same phytochemical combinations. A combination of nonacosane-10-ol and 23a-homostigmast-5-en-3β-ol inhibited egg hatching at the highest rate and  induced 100.0%  mortality of second-stage juvenile (J2) at the concentration of 100 µg ml-1. The egg hatch inhibition and J2 mortality were positively correlated with an increase in the concentrations of phytochemical as well as with the incubation time. All phytochemical mixtures displayed a nematicidal effect against M. incognita in in planta studies. The combine application of nonacosan-10-ol and 23a-homostigmast-5-en-3β-ol resulted in the highest reduction in nematode parameters (viz., galls, gall index, females g-1 of root and eggs g-1 of root) and promoted the greatest increase in the plant parameters (such as shoot and root lengths, fresh and dry shoot weights, and number of flowers plant-1) at the highest concentration of 100 µg ml-1. The phytochemical mixtures did not induce phytotoxic effects on tomato seed germination and seedling growth in in vitro tests. It was concluded from the present study that such phytochemical mixtures offer nematocidal potential in organic vegetable production systems or could be integrated with other management tools as a part of sustainable control strategies for plant-parasitic nematodes.
Keywords: Phytochemical combinations; nonacosane-10-ol; sterol; cis- and trans-protopinium; Meloidogyne incognita; tomato